The Role of Water Temperature in Hard Clam Aquaculture - Kerry Weber; Leslie Sturmer; Elise Hoover; Shirley Baker (EDIS)
FA-151, a 9-page illustrated fact sheet by Kerry Weber, Leslie Sturmer, Elise Hoover, and Shirley Baker, describes the effects of water temperature in hard clam production in Florida — how it is measured, how it affects their physiology, signs of temperature stress, and how to manage for water temperature. Includes a glossary and references. Published by the UF Department of Fisheries and Aquatic Sciences, October 2007.